Mesoporous silica coating on hierarchical flowerlike Fe2O3 with enhanced catalytic activity for Fenton-like reaction. Issue 78 (5th August 2016) - Cui, Zhi-Min; Hao, Jing; Liu, Jian; Song, Wei-Guo
Abstract : The catalytic activity of hierarchical flowerlike Fe2 O3 in the Fenton-like reaction was dramatically enhanced by the mesoporous silica coating. Abstract : Hierarchical flowerlike Fe2 O3 was coated with mesoporous silica to form a Fe2 O3 @mesoporous silica composite with a core/shell structure through a simple solution-based method with the assistance of Fe2 O3 as a precursor. When used as a catalyst for a Fenton-like reaction for the degradation of methylene blue, the Fe2 O3 mesoporous silica composite was much more active than the bare flowerlike Fe2 O3, which suggests that the catalytic activity of the flowerlike Fe2 O3 in the Fenton-like reaction was dramatically enhanced by the mesoporous silica coating.